An essential role of cAMP response element-binding protein in epidermal growth factor-mediated induction of sodium/glucose cotransporter 1 gene expression and intestinal glucose uptake. (July 2015) - Wang, Chun-Wen; Chang, Wen-Liang; Huang, Yu-Chuan; Chou, Fang-Chi; Chan, Fang-Na; Su, Shih-Chieh; Huang, Shu-Fen; Ko, Hui-Hsuan; Ko, Yi-Ling; Lin, Hang-Chin; Chang, Tsu-Chung
Graphical abstract: Highlights: EGF-induced glucose uptake is due to changes in the number of SGLT1 molecules. An essential CREB binding motif in the SGLT1 promoter for conveying EGF signals. CREB phosphorylation is essential for EGF-induced SGLT1 gene expression. The EGFR and PI3K pathways are essential in EGF-induced SGLT1 gene expression. SGLT1 level is decreased in the inflamed intestine and related with CREB deactivation. Abstract: The sodium/glucose cotransporter 1 (SGLT1) is responsible for glucose uptake in intestinal epithelial cells. Its expression is decreased in individuals with intestinal inflammatory disorders and is correlated with the pathogenesis of disease. The aim of this study was to understand the regulatory mechanism of the SGLT1 gene. Using the trinitrobenzene sulfonic acid-induced mouse models of intestinal inflammation, we observed decreased SGLT1 expression in the inflamed intestine was positively correlated with the mucosal level of epidermal growth factor (EGF) and activated CREB. Overexpression of EGF demonstrated that the effect of EGF on intestinal glucose uptake was primarily due to the increased level of SGLT1. We identified an essential cAMP binding element (CRE) confers EGF inducibility in the human SGLT1 gene promoter. ChIP assay further demonstrated the increased binding of CREB and CBP to the SGLT1 gene promoter in EGF-treated cells. In addition, the EGFR- and PI3K-dependent CREB phosphorylations are involved in the EGF-mediated SGLT1 expression. This is the first report to demonstrate that CREB is involved in EGF-mediated transcription regulation of SGLT1 gene in the normal and inflamed intestine, which can provide potential therapeutic applications for intestinal inflammatory disorders.